2016
DOI: 10.19030/cier.v9i4.9788
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Geology Concepts In Education Standards For A Rapidly Changing Global Context

Abstract: Internationally much attention is being paid to which of a seemingly endless list of scientific concepts should be taught to schoolchildren to enable them to best participate in the global economy of the 21st Century. In regards to science education, the concepts framing the subject of geology holds exalted status as core scientific principles in the Earth and space sciences domain across the globe. Economic geology plays a critical role in the global economy, historical geology guides research into prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…We then expanded our organisational structure because in recent decades in the U.S. and elsewhere, geoscience educators have devoted considerable effort to creating consensus standards and frameworks to guide geology education. Instead of ending up with a single geoscience education reform document, competing efforts have now resulted in numerous geology education standards for teachers in the US: NSES (National Research Council, 1996); Benchmarcks for Scientific Literacy (American Association for the Advancement of Science [AAAS], 1993); Earth Science Literacy Principles (2010); NGSS (2013) (Guffey, Slater, Schleigh, Slater, & Heyer, 2016;viz., Slater & Slater, 2015). As a result, instead of selecting just one of these competing frameworks to organise a contemporary review of students' misconceptions in geology, as a secondary position, we judged it would be most fruitful to create a review of misconceptions around a consensus of the U.S.'s community's overlapping ideas about which concepts should be taught in geology.…”
Section: Methodsmentioning
confidence: 99%
“…We then expanded our organisational structure because in recent decades in the U.S. and elsewhere, geoscience educators have devoted considerable effort to creating consensus standards and frameworks to guide geology education. Instead of ending up with a single geoscience education reform document, competing efforts have now resulted in numerous geology education standards for teachers in the US: NSES (National Research Council, 1996); Benchmarcks for Scientific Literacy (American Association for the Advancement of Science [AAAS], 1993); Earth Science Literacy Principles (2010); NGSS (2013) (Guffey, Slater, Schleigh, Slater, & Heyer, 2016;viz., Slater & Slater, 2015). As a result, instead of selecting just one of these competing frameworks to organise a contemporary review of students' misconceptions in geology, as a secondary position, we judged it would be most fruitful to create a review of misconceptions around a consensus of the U.S.'s community's overlapping ideas about which concepts should be taught in geology.…”
Section: Methodsmentioning
confidence: 99%
“…To successfully demonstrate the objectives, the Framework presented three dimensions: (a) Practices are what scientists and engineers use in investigation while building models, theories, and explanations about the natural world; (b) Cross-cutting concepts are an approach of connecting the different fields of science; and (c) Disciplinary core ideas identify the core knowledge in a science discipline and guide curriculum, instruction, and assessment (National Research Council, 2013). The NGSS were the first widely to incorporate systems, processes, and technology within this content (Guffey et al, 2016).…”
mentioning
confidence: 99%
“…An earlier study questioned the degree of overlap among the four national standard reform documents (Benchmarks, NSES, ESLP, and NGSS) (Guffey et al, 2016;. Results showed that not only are the standards within each individual document often redundant, but also there are only two core geology concepts that overlap: plate tectonics and the water cycle.…”
mentioning
confidence: 99%